JOYSTICK CONTROL OF A 3D PRINTED ROBOTIC MANIPULATOR FOR STUDENT LEARNING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the present work, the control mode of a robotic manipulator with a joystick when moving an object to a desired position is considered. In automated systems, it is always necessary, in addition to the main automatic mode, to have an additional mode allowing additional adjustment. In addition, it can serve to determine the most suitable trajectory for the robot's motion, both for its recording and for motion training. 3D printing technology was chosen to create the individual details of the robot, which significantly reduces its cost. The details can be restored at any time if necessary. Arduino IDE and Nano board are used as the control development platform. The project is the basis of a student's thesis on automatic control of a robotic manipulator. The finished project will serve to train students and make it easier to adopt and adapt to these modern technologies. This step-by-step project implementation approach was chosen, as it will lead to consolidation and acquisition of new knowledge at each stage of implementation.